EFFICACY OF QUINAPYRAMINE SULPHATE, ISOMETAMEDIUM CHLORIDE AND DIMINAZENE ACETURATE FOR TREATMENT OF SURRA - M. Amjad; M. H. Saleem; M. Z. Iqbal; A. Hassan; A. Jabbar; M. Ashraf; M. Qasim; A. Ullah; M. M. Tolba; H. A. Nasser; S. Naaz; I. Ahmad (Journal of Animal and Plant Sciences, 2022)
Trypanosomiasis (Surra) is a parasitic and zoonotic disease caused by Trypanosoama evansi, transmitted by insect vectors Tabanus and Stomoxys mechanically. The aim of the present study was to determine the therapeutic efficacy of various trypanosidal drugs against trypanosomiasis in Thoroughbred horses. Horses having clinical signs of trypanosomiasis were diagnosed through blood smear through a microscope were selected for this study. The infected horses were divided into three experimental groups for therapeutic trials. Animals in group A were treated with a single dose of quinapyramine sulphate @ 3000mg/ml per 50 /kg body weight; group B was treated with a single dose of isometamedium chloride Hydrochloride@ 0.5 mg/2.5 ml of 1% solution per 50/kg body weight; group C was treated with a single dose of diminazene aceturate@ 2360 mg/15 ml per 100/kg. Results revealed that significant (P<0.0001) decline in the values of erythrocyte counts (RBC), hemoglobin concentration (Hb), packed cell volume (PCV), platelets (PLT) and a significant (P<0.0001) increase in white blood cells (WBC), granulocytes, and monocytes in infected horses as compared to healthy ones. Therapeutic trials indicated that quinapyramine sulphate that showed 100% efficacy at 21th days had significantly higher than isometamedium chloride and diminazene aceturate (95.83 and 75% efficacy, respectively). The hematological parameters of recovered horses were significantly restored to normal values on day 21 after treatment. It is concluded that quinapyramine sulphate is the drug of choice against trypanosomiasis in Thoroughbred horses.
Keywords: Trypanosomiasis; Thoroughbred horses; Trypanosidal drugs; hematological effect; therapeutic efficacy